An Error Analysis on Descriptive Texts of Eleventh Grade Students at SMK Muhammadiyah 2 Surakarta 2015/2016 Academic Year - Nurishma, Auliya; , Prof. Dr. Endang Fauziati, M. Hum; , Siti Fatimah, S. Pd., M. Hum (2016)
ABSTRACT The aims of this research are: (1) to describe errors made by eleventh grade students of SMK Muhammadiyah 2 Surakarta in their writing descriptive texts, (2) identifying the types of lexical errors, grammatical errors, and discourse errors and also explain the frequency of each type of errors, and (3) describing the dominant type of errors, and identifying the sources of errors. The researcher uses qualitative research because the researcher do not set hypothesis and test it but focus on analyzing after taking the data. The researcher uses elicitation method in her research to get the data. The subject of the research is the eleventh grade students of SMK Muhammadiyah 2 Surakarta. The researcher takes erroneous on descriptive texts of eleventh grade student for the object of the research from 31 student's worksheet in writing descriptive texts. The researcher found the type of errors based on the data, they are lexical, grammatical and discourse. (1) the lexical errors level is 35 errors (10,54%), (2) the grammatical errors level is 268 errors (80,72%), and (3) the discourse errors level is 29 errors (8,75%). The highest errors that the learners made is in misordering noun phrase with the total errors is 29 errors (8,73%). Key words: errors analysis, descriptive text, sources of errors.